Penerapan Metode Electre Dan SAW Dalam Menentukan Kelayakan Penerima Bantuan Pangan Beras Bulog - Candra, Amanda Veby Dwi; Hidayati, Rahmatina (LPPM STIKI MALANG, 2024)
Poverty is a complex social problem, especially in areas where basic needs are difficult. The Indonesian government itself has developed various aid programs, including the provision of food aid in the form of rice. The provision of rice food assistance is often not on target due to various factors, including errors in collecting recipient information. The importance of determining the eligibility of Bulog rice food aid recipients by considering several criteria simultaneously to ensure that the aid is on target. This study discusses the application of the Electre and Simple Additive Weighting (SAW) method in determining the eligibility of Bulog rice food aid recipients of Sukomalo Village residents. Some of the criteria used in this study were age, employment, income level, number of children, status of home ownership, drinking water source, quality of house, and electric power. Research results show that alternative A6 has a total value of E_kl=4, referred to as a primary alternative with the Electre method, while alternative A9 has a total preference value of 18 and processed by the SAW method. Based on the results of the calculation, Bulog rice food aid recipients are on target according to the conditions and conditions of recipients who are very suitable for receiving assistance.